PEMANFAATAN DIGITALISASI UNTUK MENCETAK WIRAUSAHA MUDA DI SEPANJANG ASRI PASKA PANDEMI COVID-19 - Noerma Pudji Istyanto; Muhammad Nasrullah; Rokhmatul Insani; Yuni Qoriah Verdiana; Rizki Afifatus Sa’diyah; M. Dawud Emerulloh (JMM (Jurnal Masyarakat Mandiri), 2022)
Abstrak: Pandemi Covid-19 telah berlangsung dua tahun sejak awal tahun 2020 lalu. Hal ini ternyata berdampak tidak hanya dari aspek kesehatan, tetapi juga aspek pendidikan dan perekonomian masyarakat. Dampak pendidikan dan ekonomi inilah yang turut dirasakan oleh warga kampung Sepanjang Asri, Sidoarjo. Adapun tujuan dari kegiatan pengabdian adalah perubahan pola pikir (mindset) wirausaha (entrepreneur), pemanfaatan teknologi secara postif, sehat dan bijak yang berlanjut pada peningkatan keterampilan pemasaran digital bagi para pemuda calon pengurus karang taruna kampung mitra yang akan dibentuk. Metode yang digunakan mulai dari sosialisasi, seminar, pelatihan, penugasan hingga pendampingan digital entrepreneur kepada 30 peserta yang terdiri dari 17 remaja putra, 13 remaja putri mulai dari tingkat SMP, SMA, Kuliah mapun pemuda yang sudah bekerja. Hasil dari kegiatan pengabdian adalah perubahan mindset, peningkatan digital skill serta terbentunkya karang taruna yang menjadi wadah untuk pengembangan diri menjadi wirausaha muda dan aktif. Adapun hasil evaluasi kegiatan pengabdian berupa penyebaran kuisoner kepada mitra menunjukkan bahawasanya 87% peserta kegiatan menjawab puas dengan kegiatan pengabdian tersebut. Kesimpulan dari kegiatan pengabdian adalah permasalah remaja dan pemuda pada mitra binaan dapat teratasi dengan dibentuknya karang taruna sebagai wadah bagi para remaja dan pemuda tersebut dengan memberikan seminar entrepreneur dan pelatihan digital skill. Saran dari kegitan pengabdian adalah membuat kegiatan yang lebih variatif, konsisten dan berkelanjutan sebagai sarana pendampingan bagi eksistensi dan keberlanjutan karang taruna tersebut.Abstract: The Covid-19 pandemic has been going on for two years since the beginning of 2020. This turned out to have an impact not only on the health aspect, but also on the education and economic aspects of the community. The impact of education and the economy is also felt by the residents of the Sepanjang Asri RT 11 / RW 06, Kelurahan Sepanjang, Kecamatan Taman, Sidoarjo Regency. The problem that occurs with partners is that many teenagers and fostered youth are addicted to gadgets and their time is to play online games, unclear tiktok, hoaxes, bullying, cybercrime and other counterproducts due to the School From Home (SFH) policy. In addition, there are no youth or youth forums and activities such as youth organizations that are able to direct more productive activities to help the family's economy due to being laid off or rolling the mat due to the low purchasing power of the people. The purpose of the service activity is to change the entrepreneurial mindset (entrepreneur), use technology in a positive, healthy and wise manner which continues to improve digital marketing digital skills and prepare business plan proposals (business plan) for youth candidates for village youth organizations. Partners to be formed. The methods used range from socialization, seminars, training, assignments to assisting digital entrepreneurs to ± 30 teenagers or young foster partners. The results of the service activities are a change in mindset, increased digital skills and the formation of youth organizations that become a forum for self-development to become young and active entrepreneurs. The results of the evaluation of service activities in the form of distributing questionnaires showed that 87% of the activity participants answered that they were satisfied with the service activities. The conclusion of the service activity is that the problems of youth and youth in fostered partners can be resolved by the formation of youth organizations as a forum for these youth and youth by providing entrepreneurial seminars and digital skills training. Suggestions from service activities are to make activities that are more varied, consistent and sustainable as a means of mentoring for the continuity of the karang taruna.